Protein co-evolution, co-adaptation and interactions - Pazos, Florencio; Valencia, Alfonso (The EMBO journal, 2008)
Co‐evolution has an important function in the evolution of species and it is clearly manifested in certain scenarios such as host–parasite and predator–prey interactions, symbiosis and mutualism. The extrapolation of the concepts and methodologies developed for the study of species co‐evolution at the molecular level has prompted the development of a variety of computational methods able to predict protein interactions through the characteristics of co‐evolution. Particularly successful have been those methods that predict interactions at the genomic level based on the detection of pairs of protein families with similar evolutionary histories (similarity of phylogenetic trees: mirrortree ). Future advances in this field will require a better understanding of the molecular basis of the co‐evolution of protein families. Thus, it will be important to decipher the molecular mechanisms underlying the similarity observed in phylogenetic trees of interacting proteins, distinguishing direct specific molecular interactions from other general functional constraints. In particular, it will be important to separate the effects of physical interactions within protein complexes (‘co‐adaptation’) from other forces that, in a less specific way, can also create general patterns of co‐evolution.